12 Association between use of prehospital mechanical CPR device for out-of-hospital cardiac arrest and outcome by patient transport interval: pilot study. (26th April 2019) - Kim, JY; Moon, SW; Park, JH; ,
Abstract : Background: In this study, we aimed to investigate effect of mechanical CPR device (MechCPR) on OHCA by patient transport interval (PTI). We hypothesized MCPR is effective on survival with prolonged PTI (P-PTI). Method: This is an observational study using Korean Cardiac Arrest Research Consortium (KoCARC) data from October 2015 to Jun 2018. EMS treated OHCA presumed of cardiac etiology without field return of spontaneous circulation (ROSC) was included. Patients with less than 15 years old, with unknown information of MechCPR, PTI and outcome were excluded. Exposure was prehospital MCPR use and outcome was survival to admission. PTI was defined as time interval between scene to hospital. P-PTI was defined if PTI longer than 9 min and NP-PTI if less. Multivariable logistic regression by PTI group (reference=manual CPR) was performed to calculate adjusted odds ratios (AORs) with 95% confidence intervals (95% CIs) for outcome. Results: From total 2, 214 OHCA patients, in rate difference of survival to admission in NP-PTI group comparing no-MCPR to MCPR was −3.44% (-11.95%–5.08%) and in P-PTI −4.34% (−11.14%–2.46%). In multivariable logistic analysis, aOR was 1.63 (0.94–2.85) in NP-PTI group and 1.74 (1.14–2.67) in P-PTI group. Conclusion: For OHCA with PTI 9 min or longer, MechCPR was associated with survival to admission for patients failed to be restored in field. Based on this pilot study, further study in larger population is needed to investigate optimized use of MechCPR for survival benefit. Conflict of interest: No conflict of interest. Funding: No funding.